(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Most studies on the effect of the role of institutional quality on the relationship between foreign investment and economic growth have been carried out in Western countries. Very few studies on the above-mentioned relationships have been done in Asian countries during. This paper will be conducted in Asian countries using the following three models: Pooled OLS, Fixed effect model, and Random effect model. This paper uses secondary data from 10 Asian countries from 2011 to 2018. The empirical results show that (1): FDI has a positive effect on the economies of the countries. Asia between 2002 and 2018 (2) The quality of the state strengthens the impact of FDI on the economies of Asian countries between 2011 and 2018. These findings imply that if improving the quality of institutions, the state will attract more FDI and economic development The research paper is based on the scientific approach of quantitative methods to solve the problems posed, practical and effective service for the completion of the research purpose. The secondary data collected from the worldbank.org to create asymmetric data tables will be processed on STATA software.